Pengaruh Risiko Keuangan, Nilai Perusahaan dan Ukuran Perusahaan Tehadap Perataan Laba - Meta Nursita; Sekar Shafa Nabilah (Economic Reviews Journal, 2024)
This research aims to analyze the influence of financial risk, company value and company size on income smoothing. This research was conducted by analyzing the financial reports of companies in the Consumer Non-Cyclicals sector listed on the Indonesia Stock Exchange (BEI) during the period 2018 to 2022. The sample used in this research was 16 companies in the Consumer Non-Cyclicals sector listed on Indonesia Stock Exchange during the period 2018 to 2022 using a purposive sampling technique. The data used in this research is secondary data in the form of financial reports from each company that has been used as a research sample. Logistic regression method was used as research methodology in this study. Analysis of research results using the help of Eviews 12 software. The results of this study show that Financial Risk partially has no effect on Profit Planning, Company Value partially has no effect on Profit Smoothing, Company Size partially has an effect on Profit Planning and simultaneously Financial Risk, Company Value and Company Size influence Income Smoothing.